MOOCs and open education around the world (Routledge, 2015)
MOOCs and Open Education Around the World explores and illuminates unique implementations of MOOCs and open education across regions and nations. The book also focuses on the various opportunities as well as the dilemmas presented in this rapidly evolving age of technology-enabled learning. What are the different delivery formats, interaction possibilities, assessment schemes, and business models? What are the key controversies or issues that must be discussed and addressed? This edited collection explains MOOCs and open education trends and issues in a variety of contexts, shares key research findings, and provides practical suggestions and recommendations for the near future.